A Study of Regional Thermal Environment Quality Based on the Physical Mass Arrangement Characteristics of River Bank Settlements in Jodipan Colorful Village - Fidelista, Alya Nafisa; Nugroho, Agung Murti; Wulandari, Lisa Dwi (Fakultas Teknik Universitas Brawijaya, 2024)
Jodipan Colorful Village, originally a slum, has transformed into a popular tourist destination. This study investigates how the physical arrangement of the settlement mass and its thermal environment affect the comfort of activities in the road corridor, a critical public space utilized by both visitors and residents for tourism, commerce, and interaction. The research aims to analyze the relationship between the spatial configuration of the buildings and the thermal conditions of the area, particularly in this densely populated riverside village. Utilizing visual techniques, the study formulates criteria for the spatial arrangement of settlements, focusing on the balance of solids and voids in the layout. Thermal environment measurements are conducted to assess air temperature and humidity along the road corridor. The findings indicate that the spatial arrangement significantly impacts the thermal environment. Factors such as building density, corridor width, and proximity to the river influence temperature and humidity levels, with closer proximity to the river correlating with higher humidity and lower temperatures. These results provide insights into optimizing public space design in high-density urban environments, particularly in similar riverside settlements.